System of three collinear interface cracks in a finite size domain - Voiedilo, R.; Loboda, V. (Національний технічний університет "Харківський політехнічний інститут", 2024)
A bimaterial region, consisting of two rectangles, connected by their edges is considered. Three cracks of arbitrary length and location have appeared in the interface. It is assumed that the load applied at the outer ends of the rectangles is directed orthogonally to the interface. The Abaqus software package is used to solve the problem. A finite element mesh with thickening near the cracks and especially near their tips is created. Eight-node finite elements of the Lagrangian type are used. A series of calculations are performed on different meshes with different degrees of their thickening, which allows us to assess the dependence of the results on the mesh parameters. To simplify and speed up the modeling process, a program in Python, which is integrated into Abaqus as a script was written. This program allows us to change quickly the parameters of cracks, loads and material properties, as well as automatically create a new mesh for each configuration. The analysis focused on the consideration of the sizes of the crack region and the calculation region dependencies. It was found out that the energy release rate increases with a decrease in the relative size of the calculation region. This is especially evident for the crack tips that are closest to the boundaries of the region. For the case of a region much larger than the crack size, a comparison of numerical results with the corresponding analytical solutions was carried out and their good agreement was shown.

Розглядається біматеріальна область складена із двох прямокутників, з’єднаних по торцям однакової довжини. В областях жорсткого з’єднання виникли три тріщини довільної довжини і розташування. Вважається, що навантаження, прикладене по зовнішнім торцям прямокутників, направлене ортогонально до інтерфейсу. Для розв’язку задачі використовується програмний комплекс Abaqus. Створена сітка скінченних елементів із згущенням поблизу тріщин і особливо біля їх вершин. Використані восьмивузлові скінченні елементи лагранжевого типу. Проведено низку розрахунків на різних сітках з різним ступенем їх згущення, що дозволяє оцінити залежність результатів від параметрів сітки. Для спрощення та пришвидшення процесу моделювання була написана програма на мові Python, яка інтегрована в Abaqus як скрипт. Ця програма дозволяє швидко змінювати параметри тріщин, навантаження та властивості матеріалів, а також автоматично створювати нову сітку для кожної конфігурації. При аналізі основна увага приділялась аналізу залежності розмірів області тріщин і розрахункової області. Встановлено зростання швидкості звільнення енергії при зменшенні відносного розміру розрахункової області. Особливо це проявляється для вершин тріщин, які є найближчими до границь області. Для випадку області, набагато більшої розміру тріщин, проведено порівняння чисельних результатів з відповідними аналітичними розв’язками і встановлена їх хороша узгодженість.
Система трьох колінеарних міжфазних тріщин в області скінченних розмірів
Keywords: deformation; interface crack; crack opening; finite element method; energy release rate; напруження; деформація; тріщини; метод скінчених елементів; швидкість звільнення енергії